The Relationship Between Reading Motivation and English Literacy Achievement Among EFL Learners - Rahayu, Putri Dianing; Richard Fidal Deme Hadjon; Sakinah Aulia Rahmah; Muhammad Tahir; Suryadi Ishak (CV. Ulil Albab Corp, 2026)
This study examined the relationship between reading motivation and English literacy achievement among EFL learners. A quantitative correlational design was employed, using a reading motivation questionnaire and a standardized English literacy test administered to 30 intermediate-level students. Descriptive analysis showed that students demonstrated high literacy performance with moderate variability in reading motivation. Pearson correlation and simple linear regression revealed that reading motivation significantly predicted literacy achievement (R = 0.512, R² = 0.262, p = 0.004), indicating that 26.2% of the variance in literacy scores could be explained by motivation levels. Furthermore, an independent-samples t-test revealed no significant difference in literacy performance between male and female students (t = 0.925, p = 0.363). These findings highlight the central role of motivation in supporting literacy development in EFL contexts, suggesting that teaching practices should prioritize developing reading motivation. The study concluded that motivation is a key psychological factor influencing literacy outcomes, while gender plays no significant role in determining literacy achievement.